Integrasi sosiologi pendidikan dalam meningkatkan profesionalisme guru Pendidikan Agama Islam di Era globalisasi - Falah, Fajrul; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
This article discusses the importance of the role of educational sociology in improving the professionalism of Islamic Education Teachers (PAI) amid globalization. This study uses a descriptive qualitative method with a literature review approach. The results show that by understanding educational sociology, PAI teachers can be more sensitive to the social and cultural backgrounds of their students. This makes the learning process more meaningful and tailored to the needs of students. In this ever-changing era, the professionalism of PAI teachers is not enough to just master religious material. They also need to have the ability to adapt to social and technological developments. Therefore, combining sociological insights with Islamic values is key in shaping PAI teachers who are not only professional, but also responsive to the challenges of the times and the needs of students.